2013
DOI: 10.2478/s11756-013-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytosociological affiliation of Annex II species Tephroseris longifolia subsp. moravica in comparison with two related Tephroseris species with overlapping distribution

Abstract: Abstract:The phytosociological affiliation of Tephroseris longifolia subsp. moravica, species of European importance, was studied in relation to two closely related species of the genus Tephroseris which have overlapping distribution within the Western Carpathian Mts: T. intergrifolia and T. crispa. The main aim was to compare plant communities inhabited by the three taxa, to assess the major environmental gradients responsible for variation in their distribution and to estimate ecological indicator values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Our study confirmed that generally all studied populations of T. (Hegedüšová et al, 2013;Meindl, 2011;Pflugbeil, 2012). This could imply that phylogenetic niche conservatism limits the ecological adaptation of the T. longifolia agg.…”
Section: Ecological Differentiation Played An Important Role In Evosupporting
confidence: 89%
See 2 more Smart Citations
“…Our study confirmed that generally all studied populations of T. (Hegedüšová et al, 2013;Meindl, 2011;Pflugbeil, 2012). This could imply that phylogenetic niche conservatism limits the ecological adaptation of the T. longifolia agg.…”
Section: Ecological Differentiation Played An Important Role In Evosupporting
confidence: 89%
“…Rchb. and Tephroseris helenitis (L.) B. Nord occurring mainly in neutral to acidophilus wet meadows and fens, and Tephroseris integrifolia (L.) Holub growing mainly in nutrient‐poor dry and semi‐dry calcareous grassland and open forest communities (Hegedüšová et al., ; Meindl, ; Pflugbeil, ). This could imply that phylogenetic niche conservatism limits the ecological adaptation of the T. longifolia agg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation